Updated Bayesian network meta-analysis on the efficacy and safety of PD−1 versus PD−L1 inhibitors in first−line treatment with chemotherapy for extensive−stage small-cell lung cancer - Wang, Ke; Zheng, Chuangjie; Chen, Xinrong; Lin, Penghui; Lin, Mengge; Chen, Cuizhen; Zhai, Linzhu (Frontiers in Oncology, 2025)
ObjectiveTo compare the efficacy and safety of programmed cell death 1 inhibitors plus chemotherapy (PD-1 + Chemo) and programmed cell death ligand 1 inhibitors plus chemotherapy (PD-L1 + Chemo) for the treatment of extensive-stage small-cell lung cancer (ES-SCLC).MethodsWe performed a meta-analysis of relevant data using R software, considering overall survival (OS), progression-free survival (PFS), and grade ≥ 3 treatment-related adverse events (TRAES).ResultsPD-1 + Chemo (OS: hazard ratio [HR] 0.71; PFS: HR 0.59) and PD-L1 + Chemo (OS: HR 0.72; PFS: HR 0.73) significantly prolonged survival and did not increase the incidence of grade ≥3 TRAEs compared with chemotherapy. Indirect comparisons showed no significant difference in clinical efficacy (OS: HR 0.99, 95% CI: 0.86–1.1; PFS: HR 0.80, 95% CI: 0.61–1.0) or safety (HR 1.0, 95% CI: 0.93–1.1) between PD-1 + Chemo and PD-L1 + Chemo. Non-cumulative probability ranking plot ranking results showed that PD-1 + Chemo ranked first in OS and PFS. Patients with PD-L1 expression levels < 1%, PD-1 + Chemo showed a trend of disadvantage (OS: HR 1.3; PFS: HR 1.2), whereas for patients with PD-L1 expression levels ≥ 1%, PD-1 + Chemo showed a trend of advantage (OS: HR 0.85; PFS: HR 0.85).ConclusionsPD-1 + Chemo and PD-L1 + Chemo significantly prolonged OS and PFS in patients with ES-SCLC and did not significantly increase the incidence of grade ≥ 3 TRAES. The efficacy and safety profiles of PD-1 + Chemo and PD-L1 + Chemo appear to be similar.